Ultrastructural and Functional Properties of a Giant Synapse Driving the Piriform Cortex to Mediodorsal Thalamus Projection - Pelzer, Patric; Horstmann, Heinz; Kuner, Thomas (Frontiers in Synaptic Neuroscience, 2017)
Neocortico-thalamo-cortical loops represent a common, yet poorly understood, circuit employing giant synapses also referred to as “class I”, giant, or driver synapses. Here, we characterize a giant synapse formed by projection neurons of the paleocortical piriform cortex (PIR) onto neurons of the mediodorsal thalamus (MD). Three-dimensional (3D) ultrastructure of labeled PIR-MD terminals, obtained by using serial-section scanning electron microscopy combined with photooxidation-based detection of labeled terminals, revealed a large terminal engulfing multiple postsynaptic dendritic excrescences. The terminal contained multiple synaptic contacts, a high density of synaptic vesicles and several central mitochondria. Using targeted stimulations of single identified PIR-MD terminals in combination with patch-clamp recordings from the connected MD neuron, we found large postsynaptic currents with fast kinetics and strong short-term depression, yet fast recovery upon repetitive stimulation. We conclude that the phylogenetically old paleocortex already developed giant synaptic connections exhibiting similar functional properties as connections formed by giant neocortico-thalamic projections.